Role of recombinant human granulocyte colony-stimulating factor in development of cancer-associated venous thromboembolism in lung cancer patients who undergo chemotherapy - Cheng, Yi; Zhao, Yunfeng; Xu, Mei; Du, He; Sun, Jinyuan; Yao, Qihuan; Qu, Jianmin; Liu, Song; Guo, Xuejun; Xiong, Wei (Frontiers in Immunology, 2024)
Background The role of recombinant human granulocyte colony-stimulating factor (rhG-CSF), especially the long-acting factor in the development of cancer-associated venous thromboembolism (VTE) in lung cancer patients who undergo chemotherapy has been understudied, although the use of rhG-CSF has been reported to be associated with an increased risk of VTE. Methods We retrospectively reviewed 1,673 lung cancer patients who underwent hospitalized chemotherapy. We performed propensity score matching to offset confounding factors related to cancer-associated VTE development and classified the patients into short-acting (N = 273), long-acting (N = 273), and no rhG-CSF (N = 273) groups. The primary outcome was cumulative cancer-associated VTE development three months after all cycles of chemotherapy. Results The overall VTE incidence in the short-acting, long-acting, and no rhG-CSF groups was 5.5%, 10.3%, and 2.2%, respectively (P <0.001). The VTE incidence in the long-acting rhG-CSF group was higher than that in the short-acting (P = 0.039) and no rhG-CSF groups (P <0.001). The VTE incidence in the short-acting rhG-CSF group was higher than that in the no rhG-CSF group (P = 0.045). The use of rhG-CSF (hazard ratio [HR] 2.337; 95% confidence interval [CI] [1.236–5.251], P = 0.006) was positively correlated with VTE development among all patients, whereas the use of long-acting rhG-CSF (HR 1.917, 95% CI [1.138–4.359]; P = 0.016), was positively correlated with VTE development in patients receiving rhG-CSF. Conclusion The use of rhG-CSF, especially long-acting rhG-CSF, increases the risk of cancer-associated VTE development compared to no rhG-CSF use in lung cancer patients who undergo hospitalized chemotherapy.